RESPON BEBERAPA VARIETAS PADI LOKAL (Oryza sativa L.) TERHADAP AMELIORAN ABU JANJANG SAWIT PADA LAHAN GAMBUT - Safrida Safrida; Nana Ariska; Yusrizal Yusrizal (Universitas Teuku Umar, 2019)
This study aims to determine the response of several local rice varieties to the provision of palm oil bare ash on peatlands. This study was arranged in a Split Plot Design Split plot with 2 treatments and 4 groups, consisting of 4 local rice varieties, namely: P 1 = Cut Krusek, P 2 = Ramos Mirah, P3= Sambe and P4= Bo Sireutoh. Ameliorant factors in palm oil ash consist of: A 0 = Control, A 1 = 15 tons ha-1. The results showed that the varieties had a very significant effect on plant height at 45 HST, number of tillers per clump age 45 HST, number of productive tillers per clump, significantly affected plant age 60 HST, had no significant effect on plant height at 30 HST, number of tillers per family age 30 and 60 HST, rice grain and grain are empty. The Bo Sireutoh variety (P 4 ) has the ability to increase the rate of growth of the number of tillers per clump, the number of productive tillers per clump and the weight of rice paddy per plot. Whereas the Cut Krusek variety (P 1 ) has the ability to increase the rate of growth at the plant height level and the percentage of empty grain. The treatment of oil palm ash ameliorant on peatland is able to increase growth at plant height, rice grain percentage and percentage of empty grain, but it does not significantly affect the number of productive tillers per clum. Keywords : Palm-length ash ameliorates, Rice Varieties